Between Discourse and Practice: Strategic Decision-Making and the Governance of Sustainability in Chilean State Universities - Abello-Romero, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study explores how the leadership of Chilean state universities integrates sustainability into their strategic decision-making processes. Employing a qualitative research approach using semi-structured interviews conducted across nine institutions, it analyzes the perspectives of rectors (equivalent to university presidents in Chilean higher education), vice-rectors, and members of university governing bodies. The findings reveal that although sustainability is present in institutional discourse, its actual implementation remains limited, fragmented, and subordinated to financial imperatives. Contextual constraints, adaptive rationalities, and limited stakeholder engagement shape strategic decisions. Furthermore, institutions often employ sustainability as a rhetorical or compliance-driven narrative rather than as a transformative governance principle. This study frames these findings through stakeholder theory, organizational sustainability, strategic rationality, and information governance. It concludes that embedding sustainability meaningfully in university governance requires institutional transformation-moving beyond symbolic commitments towards inclusive, evidence-driven, and participatory decision-making practices.